VIRULENSI NUCLEAR POLYHEDROSIS VIRUS (NPV) TERHADAP ULAT GRAYAK (Spodoptera litura F.) (Lepidoptera : Noctuidae) PADA TANAMAN TEMBAKAU DELI DI RUMAH KACA - Ade Sartika Rimadhani; Darma Bakti; Maryani Cyccu Tobing (Universitas Sumatera Utara, 2013)
Spodoptera litura (Lepidoptera : Noctuidae) is one important of pests on Deli tobacco. This researchwas study the virulence of Nuclear Polyhedrosis Virus of larvae S. litura on Deli tobacco inGlasshouse. This research was carried out at Central Research Deli Tobacco Sampali PTPN IIMedan from May to September 2012. The method of this research was Randomized CompleteDesign Factorial which consists stages of larvae (2nd and 4th instar) and the number of virussuspenses (10, 20, and 30 larvae infected virus/1 l water) with three replications. The results showedthat highest percentage mortality (91.67%) was found in treatment 2nd instar with suspense 30 larvaeinfected virus/1 l water and the lowest percentage (0%) on control. The highest percentage ofdamage intensity (33.06%) was control and the lowest percentage (15.58%) on suspense 30 larvaeinfected virus/1 l water. The fastest incubation period in the treatment 4th instar are I.67 days andsuspense of 30 larvae infected virus/1 l water are 1.83 days and the lowest in the treatment 2nd instarare 2.58 days and control didn’t showed symptoms infection.Keywords : Spodoptera litura, NPV, virulence